The Combined Extract of Purple Waxy Corn and Ginger Prevents Cataractogenesis and Retinopathy in Streptozotocin-Diabetic Rats. (31st December 2014) - Thiraphatthanavong, Paphaphat; Wattanathorn, Jintanaporn; Muchimapura, Supaporn; Thukham-mee, Wipawee; Lertrat, Kamol; Suriharn, Bhalang
Abstract : Based on the crucial roles of oxidative stress and aldose reductase on diabetic complications and the protective effect against diabetic eye complication of purple waxy corn and ginger (PWCG) together with the synergistic effect concept, we aimed to determine anticataract and antiretinopathy effects of the combined extract of purple waxy corn and ginger (PWCG). The streptozotocin diabetics with the blood glucose levels >250 mg·dL −1 were orally given the extract at doses of 50, 100, and 200 mg/kg·BW −1 for 10 weeks. Then, lens opacity and histopathology of retina were determined. The changes of MDA together with the activities of SOD, CAT, GPx, and AR in lens were also determined using biochemical assays. All doses of PWCG decreased lens opacity, MDA, and AR in the lens of diabetic rats. The elevation of CAT and GPx activities was also observed. The antiretinopathy property of the combined extract was also confirmed by the increased number of neurons in ganglion cell layer and thickness of total retina and retinal nuclear layer in diabetic rats. PWCG is the potential functional food to protect against diabetic cataract and retinopathy. However, further studies concerning toxicity and clinical trial are still essential.